AI and robotics in the European restaurant sector: Assessing potentials for process innovation in a high-contact~service industry - Katharina Blöcher; Rainer Alt (Electronic Markets, 2020)
The restaurant technology market is rapidly evolving and is transforming the restaurant business as a significant sector of tourism and hospitality. Enabled by artificial intelligence (AI), mobile apps, kiosks and chatbots revolutionize the guest experience and robots automate restaurant operations. Despite the increasing interest, the use of AI and robotics in restaurants is still in its early stage and restaurant managers are seeking guidance to leverage these technologies~for service excellence. In this high-contact service sector, emotional skills need to be balanced with the possible automation potentials. The present research~analyzes the current state of AI and robotics in the restaurant sector~and proposes a systematic identification of process innovation potentials. For this purpose, a market analysis of the European AI and robotics market for restaurant operations~is conducted, which yields a first knowledge base for future research and conceptual work. Besides~detailed empirical data, a reference process~is developed for leveraging new technologies for process innovation.
Keywords: L86; O14; 620; Artificial intelligence; Robotics; Restaurant industry; Restaurant technology; Smart tourism